2013
DOI: 10.1111/lam.12148
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of endodontic applications of ozone and low-temperature atmospheric pressure plasma on root canals infected with Enterococcus faecalis

Abstract: Significance and Impact of the Study: The present study handles different perspectives on chemomechanical preparation of root canals. Ozone and low-temperature atmospheric pressure plasma (LTAPP) were investigated to determine whether they could be an alternative for NaOCl. Up to now, chemical solutions (NaOCl, chlorhexidine digluconate, etc.…) have been used to disinfect the root canals. When the reported effects of LTAPP on biological and chemical decontamination were taken into consideration, a question ros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 40 publications
(73 reference statements)
0
19
0
1
Order By: Relevance
“…The values for the coronal, middle and apical third were 3.2 log10, below detection level and 3.4 log10, respectively. This shows that the antibacterial effect can be substantiated over the total length of the root canal [50]. E. faecalis is capable of penetrating the radial dentin tubuli up to 1000 µm [7] and may reinfect the filled root canal system after the primary treatment.…”
Section: Discussionmentioning
confidence: 83%
“…The values for the coronal, middle and apical third were 3.2 log10, below detection level and 3.4 log10, respectively. This shows that the antibacterial effect can be substantiated over the total length of the root canal [50]. E. faecalis is capable of penetrating the radial dentin tubuli up to 1000 µm [7] and may reinfect the filled root canal system after the primary treatment.…”
Section: Discussionmentioning
confidence: 83%
“…Studies have shown the important efficacy of aqueous ozone 18 especially when associated with ultrasonic activation 10 , 17 . The efficacy is statistically comparable to the highest concentrations of sodium hypochlorite 10 , 14 .…”
Section: Introductionmentioning
confidence: 99%
“…So far, different studies were performed with plasma devices like plasma jets and direct dielectric cold plasma devices, to affect E . faecalis , as organism of the ESKAPE pathogen group [53, 54]. Modic et al .…”
Section: Discussionmentioning
confidence: 99%